KECAKAPAN ABAD 21: KOMPETENSI DIGITAL GURU DALAM MEMBUAT MEDIA PEMBELAJARAN BERBASIS ANDROID - Sari Saraswati; Iesyah Rodliyah; Novia Dwi Rahmawati (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2023)
Abstrak Community service activities are caused by several factors, such as changes in the learning process and technological developments in learning media. Based on these problems, training is needed for teachers of MTs Salafiyah Syafi'iyah Tebuireng Jombang regarding digital learning media. This training aims to assist the teachers of MTs Salafiyah Syafi'iyah Tebuireng in developing interactive android-based learning media that can be used and used remotely. This training is conducted face to face in the multimedia laboratory room. Service activities are carried out in stages starting from preparation, implementation, evaluation and reporting. Participants in the community service activity totaled 20 people from various subject teachers. Before and after the completion of the training activities, all participants were asked to complete a test consisting of 20 multiple choice questions. This test aims to see an increase in the ability of participants in designing Android-based interactive learning media. The test results showed that there was an increase between the pretest and posttest results. The posttest results showed that 90% of the participants scored above the KKM. This shows that the ability of the participants shows that the digital competence of teachers increases after being given training in designing android-based learning media. Kata kunci: 21st century learning, interactive learning media, android.